2016
DOI: 10.1016/j.jsat.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Personal Network Structure and Substance Use in Women by 12Months Post Treatment Intake

Abstract: Introduction Women with substance use disorders enter treatment with limited personal network resources and reduced recovery support. This study examined the impact of personal networks on substance use by 12 months post treatment intake. Methods Data were collected from 284 women who received substance abuse treatment. At six month follow up, composition, support availability and structure of personal networks were examined. Substance use was measured by women’s report of any use of alcohol or drugs. Hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 59 publications
0
20
1
1
Order By: Relevance
“…103,104 For example, substance abuse is an individual-level behavior that is a risk factor for all forms of violence 8,13,15,42,72,76,105,106 and also a health outcome that is linked to risk factors at the community and relationship levels such as neighborhood poverty 107 and lack of social support. 108 Other risk factors at the individual level that are associated with increased risk for perpetration of almost all forms of violence include low educational achievement 5,42,76,79,109,110 lack of nonviolent coping skills, 5,18,27,75,76,79,80,111 poor behavioral control/impulsiveness, 5,18,29,52,75,76,79,111 history of violent victimization, 8,1013,18,42,112 witnessing violence, 18,29,52,76,94,113,114 and psychological or mental health problems. 8,12,13,18,42,76,115 Conversely, improvements in nonviolent problem-solving skills have been found to be protective against perpetration of some forms of violence including child abuse and neglect, 116 teen dating violence, 117 youth violence, 118 and suicide.…”
Section: Risk and Protective Factors Across The Social Ecology*mentioning
confidence: 99%
“…103,104 For example, substance abuse is an individual-level behavior that is a risk factor for all forms of violence 8,13,15,42,72,76,105,106 and also a health outcome that is linked to risk factors at the community and relationship levels such as neighborhood poverty 107 and lack of social support. 108 Other risk factors at the individual level that are associated with increased risk for perpetration of almost all forms of violence include low educational achievement 5,42,76,79,109,110 lack of nonviolent coping skills, 5,18,27,75,76,79,80,111 poor behavioral control/impulsiveness, 5,18,29,52,75,76,79,111 history of violent victimization, 8,1013,18,42,112 witnessing violence, 18,29,52,76,94,113,114 and psychological or mental health problems. 8,12,13,18,42,76,115 Conversely, improvements in nonviolent problem-solving skills have been found to be protective against perpetration of some forms of violence including child abuse and neglect, 116 teen dating violence, 117 youth violence, 118 and suicide.…”
Section: Risk and Protective Factors Across The Social Ecology*mentioning
confidence: 99%
“…In these families, substance-using behaviors are normalized, drug use initiation is common, and use is often a marker of transition to adulthood (Hedges, 2012). This is further demonstrated through social networks where the number of other substance users in a woman’s network can predict the severity of her substance use (Tracy et al, 2016). Considering the close-knit networks which characterize the cultural uniqueness of rural Appalachia (Jones, 2010), associations of relationships and drug use among women is an important area of study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated the density of social networks are closely associated with risk behavior norms in both sexual [40,41] and drug risk behavior [15]. Furthermore, one study found that denser social networks were associated with a lower likelihood of substance use among women one year after treatment [42], while another [43] found social network density inversely associated with problem drinking. Similarly, the protective effect found in the current study may potentially be explained by increases in social support -or perhaps the increase in norm enforcement and social monitoring provided in dense networks.…”
Section: Discussionmentioning
confidence: 97%